Seed sourcing strategies for ecological restoration under climate change: A review of the current literature - Vitt, Pati; Finch, Jessamine; Barak, Rebecca S.; Braum, Anna; Frischie, Stephanie; Redlinski, Izabella (Frontiers in Conservation Science, 2022)
Climate change continues to alter the seasonal timing and extremes of global temperature and precipitation patterns. These departures from historic conditions along with the predicted variability of future climates present a challenge to seed sourcing, or provenance strategy decisions, within the practice of ecological restoration. The “local is best” for seed sourcing paradigm is predicated upon the assumption that ecotypes are genetically adapted to their local environment. However, local adaptations are potentially being outpaced by climate change, and the ability of plant populations to naturally migrate or shift their distribution accordingly may be limited by habitat fragmentation. Restoration practitioners and natural area managers have a general understanding of the importance of matching the inherent adaptations of source populations with the current and/or future site conditions where those seeds or propagules are planted. However, for many species used in seed-based restoration, there is a lack of empirical evidence to guide seed sourcing decisions, which are critical for the longevity and ecological function of restored natural communities. With the goal of characterizing, synthesizing, and applying experimental research to guide restoration practice, we conducted a systematic review of the literature on provenance testing of taxa undertaken to inform seed sourcing strategies for climate resiliency. We found a strong bias in the choice of study organism: most studies have been conducted on tree species. We also found a strong bias regarding where this research has been conducted, with North America (52%) and Europe (31%) overrepresented. Experiments were designed to assess how propagule origin influences performance across both climatic (26%) and geographic (15%) distance, with some studies focused on determining how climate normal conditions (39%) impacted performance related to survivorship, growth and other parameters. We describe the patterns and gaps our review identified, highlight specific topics which require further research, and provide practical suggestions of immediate and longer-term tools that restoration practitioners can use to guide and build resilient natural communities under future climate scenarios.